Oral malignant melanoma - Y C Chaitanya; P Vinil Chaitanya; M Venkat Reddy; B Bhavya (Wolters Kluwer Medknow Publications, 2018)
Primary malignant melanoma of the oral cavity is a rare neoplasm. In this article, we report the case of a 55-year-old woman with primary malignant melanoma of the maxillary gingiva. Based on the clinical and histopathological examination, a final diagnosis of malignant melanoma was given. Despite its rarity, melanoma is the most important pigmented lesion of oral cavity because of its deadly nature. Early detection and treatment are essential for better prognosis in mucosal malignant melanoma.